OLANZAPINE COMBINED WITH STANDARD ANTIEMETIC REGIMENS FOR PREVENTION OF CHEMOTHERAPY THERAPY-INDUCED NAUSEA AND VOMITING: A SINGLE-CENTER EXPERIENCE FROM SOUTH INDIA - James, Emmanuel; Pm, Drisya; Jose, Wesely M (Asian Journal of Pharmaceutical and Clinical Research, 2017)
Â  Â Objectives: Olanzapine, an antipsychotic agent, exhibits significant antiemetic properties due to its inhibitory activity on neurotransmitters at multiple receptors involved in chemotherapy-induced nausea and vomiting (CINV). CINV can have an immensely negative impact on patient's quality of life (QOL) and daily activities. Our objectives were to determine the effectiveness of adding olanzapine to standard antiemetic regimens for the prevention of CINV in cancer patients and to compare the QOL of such patients with those receiving standard antiemetic regimens. Methods: A prospective, observational, cohort study was done on patients receiving either highly or moderately emetogenic chemotherapy (MEC). The patients who received only the standard antiemetic regimens were considered as the control group and those who received 10 mg of olanzapine once daily on days 1-5 of chemotherapy in addition to the standard antiemetic regimens were considered to be the study group. The patients were assessed for grades of nausea and vomiting using National Cancer Institute common terminology criteria for adverse events and for QOL using European Organization in Research and Treatment of Cancer QOL questionnaire. Results: Patients were evaluated for a total of 168 cycles of chemotherapy. Compared to the control group, the study group patients showed significant improvement in response to acute nausea (p=0.02) but not in acute vomiting (p=0.09). However, response to delayed nausea and vomiting improved significantly (p=0.004 and p=0.05, respectively). The QOL of study group patients showed significant improvement in functional scales and symptom scales (p<0.02). Global health status also increased significantly (p=0.02) in the study group patients. Conclusion: Olanzapine containing pre-medication regimens can reduce acute and delayed nausea and delayed vomiting and improve the QOL of cancer patients receiving highly or moderately emetogenic chemotherapeutic agents as compared to the standard pre-medication regimens.